A Router based Hybrid Approach for Congestion Control in High speed Wired Networks - Kushwaha, V; Gupta, R (International Journal of Computer Sciences and Engineering, 2025)
Efficient management of congestion problem in High speed wired networks is a challenging issue due to higher bandwidth, large queuing delay, high burstiness and heterogeneous traffic flows. In this paper a hybrid router based mechanism New-Fair-Queuing-CoDel (nfqCoDel) has been proposed by incorporating the functionality of both, a packet scheduler and active queue manager in a single module called ‘Fair Active Queue Manager (FAQM)’. nfqCoDel actively manage the router queue length with an objective to control the excessive delay experienced by source host and maintain the weighted fairness among different hosts. Thus nfqCoDel is able to solve the buffer-bloat issue while providing weighted fairness among different sources. Simulation results, implemented in NS-2, prove that ‘nfqCoDel’ performs better than other AQMs by providing maximum and stable throughput, stable average queue length, controlled delay at router buffer and weighted fairness among competing traffic sources